Bioremediation techniques as affected by limiting factors in soil environment - Alori, Elizabeth Temitope; Gabasawa, Alhasan Idris; Elenwo, Chinyere Edna; Agbeyegbe, Oluwadolapo Ololade (Frontiers in Soil Science, 2022)
Soils are polluted by both organic and inorganic substances. Plants growing in polluted soils suffer damages such as leaf rolls, chlorosis, growth inhibition, root tips browning, and, death of plant. Soil pollutants such as hydrocarbon and heavy metals are absorbed by crops and such ends up being consumed by human posing health risk like cancer and respiratory abnormally. Conventional methods of remediation such as chemical and physical methods are very expensive and not sustainable. Excavation which is a type of physical method merely shifts the pollutant from one site to another. Bioremediation is a biological method of reclaiming polluted soils. Bioremediation is less expensive and more sustainable and safer compared to the chemical and physical methods of reclamation of polluted environment. Bioremediation is an extremely attractive, important and productive alternative for cleaning, debugging, managing and rehabilitating and consequently ameliorating contaminated environments via judicious utilisation microbial activities. The rate at which the waste substances are degraded is usually dictated by competitiveness amongst biological agents, sub-optimal supply of essential nutrients, unconducive abiotic conditions (in forms of temperature, aeration, pH and moisture); and constrained pollutant‘s bioavailability. Bioremediation is often effective only under conducive environmental conditions favourable for the growth and activities of microorganisms. It has been used at diverse locations the world over with various success stories. Based on the significance of bioremediation in enhancing the reclamation of environments by decontaminating and degrading heavy metals and xenobiotics, more focussed researches would be needed so as to improve environments in terms of containing pollutants in much safer ways and conditions through bioremediation techniques. Environmental, and other, factors not easily controlled and that can mar effective efficacy bioremediation techniques should also be decisively tackled. This research discussed the various types and methods of bioremediation. The mechanisms actions and strategies of microorganisms in bioremediation were well expatiated.